DESCRIPTION OF BLOOD GLUCOSE LEVELS BASED ON SELF-MANAGEMENT DIABETES AND DIETARY COMPLIANCE OF PATIENTS WITH TYPE 2 DIABETES MELLITUS IN WANGAYA HOSPITAL, DENPASAR - Ni Kadek Pingky Pebriana; Gusti Ayu Dewi Kusumayanti (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2020)
Diabetes mellitus is  metabolic disorder disease characterized by increase blood sugar due to insulin resistance. The objective of this study is determine description of blood glucose levels based on diabetes self management and dietary compliance outpatients with type 2 diabetes. Type of research used in this study was observational with a cross-sectional approach. Place of research is in Wangaya Hospital Denpasar. Research sample amounted to 33 people with a sampling technique  is non random sampling with purposive method. From the results of cross table description of blood glucose levels based on diabetes self-management, who have good diabetes self-management with controlled blood glucose are 3 people (42,9%) and 3 people (11,5%) not controlled. This indicates someone who has good self-management tends to have controlled blood glucose than uncontrolled. When viewed from cross table description of picture of blood glucose based on dietary compliance, it was who complianced  diet with controlled blood glucose were as many as 1 person (14,3%). While who uncomplianced the diet were as many as 6 people (85,7%) with controlled blood glucose and 26 people (100%) uncontrolled. The conclusion is that someone who has good self-management and adheres to a diet tends to have controlled blood glucose levels.Keywords: Blood Glucose Level, Self Management Diabetes, Diet Adherence, Type 2 Diabetes Mellitus